O lirismo na gravura abstrata de Fayga Ostrower - Tavora, Maria Luisa Luz (1990)
The prints by Fayga Ostrower, produced since the fifties, has assumed a conspicuous position compared to the abstract art developed in Brazil. Her prints represent the most personal approach within abstraction, usually known as "informal". In our country, Fayga was the pioneer of the abstract printmaking. The main characteristic of the work is the relationship of the structure of the grafhic patern with the use of colour as a fundamental element construct the image. Her etchings and woodcuts bring up poetry and lyricism. The interrelationship of planes of coloured transparencies created by the over printing the woodblocks contributes to the building up of this lyricism. The transparencies bring up a dynamic sight which suggests to the eye an exercice of perception. In her "lyrical engineering" conception, wisdom and sensibility are tied up, and from this meeting poetry springs from the prints.